А teenager's psychological potential actualizing model in the children's health and recreation facility developmental environment (Educational Dimension, 2023)
The article is devoted to an empirical study of the intersubjective interaction nature influence in the children's health and recreation facility developmental environment on the individual's psychological potential manifestation specifics in adolescence. The teenager's psychological potential actualizing model was developed and tested based on the research. The aim of the study is to research the development and implementation specifics of the teenager's psychological potential actualization model in temporary developmental environment children's groups. The adolescents' psychological potential specific manifestations structural characteristics study was conducted in 2017-2022. 2022 teenagers participated in the experiment on a voluntary basis and anonymously. Methods. The study has a longitudinal cyclical nature. Quantitative assessment methods were used: sociometric survey (J. Moreno) and emotional intelligence assessment (N. Hall); and qualitative assessment: a stories-narratives "My Potential" hermeneutic study. Theoretical analysis methods, scientific material synthesis and systematization according to the research aim, obtained results quantitative and qualitative assessment comparative methods were also used. Results. The study showed actualizing the adolescent's psychological potential introducing effectiveness technology into the children's health and recreation facility developmental environment. The intersubjective interaction developmental environment is organized to increase the emotional intelligence level, improve the individual's social status in the group, which activates the adolescent's psychological potential components development (motivational, behavioural, emotional and value), according to the development social situation and through the leading activities implementation. Conclusions. The adolescent's psychological potential actualization model application has been developed and substantiated. Forms and methods of developmental work with teenagers according to the competence approach are outlined. There are significant results in the adolescent's psychological potential increasing indicators regarding the components direction.
Keywords: developmental environment; teenagers; teenagers' life spheres (emotional, motivational, behavioural, interpersonal communication, physical condition); personality's psychological potential; teenagers' motivational potential in educational activities